Review of photodynamic therapy in actinic keratosis and basal cell carcinoma - Marica B Ericson; Ann-Marie Wennberg; Olle Lark&ouml (Dove Medical Press, 2008)
Marica B Ericson1,2, Ann-Marie Wennberg1, Olle Larkö11Department of Dermatology; 2Department of Physics, Göteborg University, Göteborg, SwedenAbstract: The number of non-melanoma skin cancers is increasing worldwide, and so also the demand for effective treatment modalities. Topical photodynamic therapy (PDT) using aminolaevulinic acid or its methyl ester has recently become good treatment options for actinic keratosis and basal cell carcinoma; especielly when treating large areas and areas with field cancerization. The cure rates are usually good, and the cosmetic outcomes excellent. The only major side effect reported is the pain experienced by the patients during treatment. This review covers the fundamental aspects of topical PDT and its application for treatment of actinic keratosis and basal cell carcinoma. Both potentials and limitations will be reviewed, as well as some recent development within the field.Keywords: photodynamic therapy, actinic keratosis, basal cell carcinoma